2020
DOI: 10.1101/2020.12.22.20245407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Privacy-first health research with federated learning

Abstract: Privacy protection is paramount in conducting health research. However, studies often rely on data stored in a centralized repository, where analysis is done with full access to the sensitive underlying content. Recent advances in federated learning enable building complex machine-learned models that are trained in a distributed fashion. These techniques facilitate the calculation of research study endpoints such that private data never leaves a given device or healthcare system. We show on a diverse set of he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Other proposed solutions to improving data sharing include promising new technologies, such as synthetic data or federated learning [ 53 – 55 ], which have been suggested to potentially help researchers publicly sharing health data while better managing the risk of deidentification. However, linkage risk will always remain a concern as even releasing summary statistics alone constitutes a certain loss of privacy for the contributing data sources in terms of differential privacy [ 28 , 56 ].…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Other proposed solutions to improving data sharing include promising new technologies, such as synthetic data or federated learning [ 53 – 55 ], which have been suggested to potentially help researchers publicly sharing health data while better managing the risk of deidentification. However, linkage risk will always remain a concern as even releasing summary statistics alone constitutes a certain loss of privacy for the contributing data sources in terms of differential privacy [ 28 , 56 ].…”
Section: Potential Solutionsmentioning
confidence: 99%
“…However, experiences collected in one institution, or geographical region are seldom sufficient to solve diverse problems, especially for rare conditions. Yet, vast amount of data collected across institutions remain in silos where they are collected [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Federated learning (FL) has emerged as a promising distributed learning approach, where the parties keep their raw data on their premises and exchange intermediate model parameters 9,10 . This approach has enabled collaborative learning for several medical applications, and it has been shown that FL performs comparably to centralized training on medical datasets [11][12][13] . Recently, the concept of swarm learning (SL) has been proposed; it enables decentralized machine learning for precision medicine.…”
Section: Introductionmentioning
confidence: 99%